The core hypothesis of rent seeking: theoretical and empirical inconsistencie - Ferrari, Vinícius Eduardo (2011)
The expression rent seeking refers to the competitive appropriation of rents originated from the state intervention in the economy. Underlying this idea, is the assumption of full rent dissipation or, in other words, the presumption that state intervention could generate artificial rents and that the pursuit of these economic transfers by private agents could promote waste of productive resources similar to the original value of the rents created by the state action. Through this present article, the author intends to demonstrate that this scenario of total dissipation is an isolated occurrence, and not a general property inherent to state action. It is possible to conclude that the theory of rent seeking is incapable of producing general analytical results. Hence, there is clear fragility of political decisions when based in this theory.